PREDICTION OF ANTIFUNGAL ACTIVITY OF OCIMUM SANCTUM TARGETING VULVO-VAGINAL CANDIDIASIS USING COMPUTATIONAL DOCKING TECHNIQUES - Manisha Tripathy , Prabhasinee Sahoo , Sangeeta Chhotaray , Soumya Ja (International Journal of Modern Agriculture, 2020)
Phytochemicals are non-nutritive plant-based compounds which are known to have therapeutic properties. Ocimum sanctum is popular due to the presence of many medicinal qualities in it. This plant extract contains various phytochemicals that help maintain in medicinal value. Candidiasis, caused by Candida sp. has emerged as a common fungal infection there days. One of the key enzymes that is involved in its metabolic pathway is dihydrofolate reductase. The molecular docking of the phytochemicals that were screened from Ocimum sanctum was carried out against the enzyme from Candida sp using BIOVIA Discovery Studio. The efficiency of the interaction between the ligand and the protein was evaluated based on -CDocker energy and -CDocker interaction energy. High positive values for the selected parameters indicated that phytochemicals such as, apigenin, cirsilineol, cirsimaritin, eugenol, luteolin, rosmarinic acid can effectively deactivate the enzyme thereby interrupting the life cycle of Candida